HOW TO TEACH ENGLISH EASILY TO STUDENTS LEARNING ENGLISH AS A SECOND LANGUAGE - Nasiba Maxmanazarovna, Ibragimova (Educational Research in Universal Sciences, 2022)
Teaching sports to students who’re intermediate proficiency and higher is incredibly fun because you’re able to use more real material in your lessons. Even your beginner students who have developed the basic reading skills to understand the gist of newspaper articles can benefit from this activity, provided you condense the stories and simplify any difficult language.